Suitability of BovineSNP50 BeadChip for the evaluation of the Cervidae family diversity - R. Kasarda; N. Moravčíková; V. Šidlová; A. Trakovická; O. Kadlečík; J. Pokorádi; R. Židek (Czech Journal of Animal Science, 2015)
Polymorphic SNPs were identified using BovineSNP50 BeadChip in three groups of cervids: farmed Red deer (n = 3), and free range Red deer (n = 5) and Fallow deer (n = 2). From the total of 54 609 SNPs, 53.85% could be genotyped. Out of 28 502 successfully genotyped autosomal SNPs only 5.3% were polymorphic. The average minor allele frequency within cervids was 0.23 (number of polymorphic SNPs ranged from 467 to 686). Results of the molecular variance analysis showed that 67.38% of variation occurred within individuals and the rest was explained by a species difference (FST = 0.32). The value of FIT (0.33) indicated a higher proportion of homozygote genotypes in the analyzed dataset. Pairwise FST values showed very clearly the genetic differentiation between Red and Fallow deer which ranged from 0.06 (farmed and free range deer) to 0.74 (farmed Red and Fallow deer). A similar result was found for Nei's genetic distances that ranged from 0.01 (among Fallow deer) to 0.79 (among farmed Red and Fallow deer). The genetic differentiation of the analyzed cervid species was evaluated also by the principal component analysis with the involvement of 6 other species from the family Cervidae, which showed a division of the Cervidae cluster into 7 subpopulations. The panels of SNPs primarily produced for a model species are becoming the marker of choice for the application in other species, but the best methods of their discovery, validation, and genotyping in non-model species need further investigations.